2015
DOI: 10.1037/a0038719
|View full text |Cite
|
Sign up to set email alerts
|

Combining seeking safety with sertraline for PTSD and alcohol use disorders: A randomized controlled trial.

Abstract: Objective The current study marks the first randomized controlled trial to test the benefit of combining Seeking Safety (SS), a present-focused cognitive behavioral therapy for co-occurring posttraumatic stress disorder (PTSD) and alcohol use disorder (AUD), with sertraline, a front-line medication for PTSD shown to also impact drinking outcomes. Method Sixty-nine participants (81% female; 59% African American) with primarily childhood sexual (46%) and physical (39%) trauma exposure, and drug dependence in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 67 publications
1
60
0
Order By: Relevance
“…With the exception of Healing our Women ( HOW ), few of these interventions are culturally congruent. 57,58,63 Additionally, few studies have examined the efficacy of combined pharmacotherapy and behavioral interventions for the syndemic, 67,68 however, those studies suggest that combined interventions are clinically warranted. Evidence generally supports the use of selective serotonin reuptake inhibitors for PTSD and other trauma-related conditions, such as depression and anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of Healing our Women ( HOW ), few of these interventions are culturally congruent. 57,58,63 Additionally, few studies have examined the efficacy of combined pharmacotherapy and behavioral interventions for the syndemic, 67,68 however, those studies suggest that combined interventions are clinically warranted. Evidence generally supports the use of selective serotonin reuptake inhibitors for PTSD and other trauma-related conditions, such as depression and anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Hien et al (2004) found that both SS and relapse prevention therapy resulted in significant reductions in substance use compared to standard community treatment. Additionally, Hien et al (2015) reported that SS, combined with either sertraline or placebo, showed significant reductions in alcohol symptoms at the end of treatment, which was sustained through 12-months follow-up. Furthermore, TREM has been shown to significantly reduce alcohol and drug abuse severity but not PTSD symptoms compared to TAU (Fallot, McHugo, Harris, & Xie, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…In general, these treatments show positive outcomes in improving patients’ PTSD symptoms and/or other symptom areas. Specifically, treatments such as ICBT, TREM, and COPE showed greater improvements in PTSD symptoms compared to control conditions (Hien et al, 2015; Najavits & Hien, 2013). The results of the efficacy of SS are mixed with one study finding no differences between SS and an active comparison health education group in terms of PTSD symptom reductions or substance use outcomes (Hien et al, 2009).…”
mentioning
confidence: 96%
“…In a recent randomized controlled trial, Hien et al (2015) tested the benefits of combining Seeking Safety with sertraline, a frontline medication for PTSD shown also to affect drinking outcomes. Both groups demonstrated significant improvements in PTSD symptoms (Hein et al, 2015).…”
Section: The Indigenous Healing and Seeking Safety Implementation Promentioning
confidence: 99%